Pemikiran Pendidikan Muhammad Atthiyah Al-Abrasyi dan Relevansinya dengan Sistem Pendidikan Islam di Indonesia - M Thoyyib (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Education is an inseparable part of human life. If we look at the agenda of universal problems faced by humans today, both the suppression of human rights, the phenomenon of violence, multicultural-religious and religious realities, narcotics abuse, unfair competition among students, poverty and especially backwardness, then the most interesting discourse for discussed is education. Education is what has always been and is always most responsible for developing it. On a national scale, approximately 27 million people in Indonesia are still wallowing in poverty, labor rights, farmers (mainly those with low education) have not been fully fulfilled, and human resources still require a lot of 'policies and means'. All of this is an educational homework that is almost never finished. Keyword. Education, multicultural-religious and Muhammad Atthiyah Al-Abrasyi